Aspen-HYSYS Simulation of Natural Gas Processing Plant - Roy, Partho S; Amin, M Ruhul (Journal of Chemical Engineering, 2012)
In this time of energy crisis low production rate against the increasing demand of the gas production regularly hampers both the domestic and industrial operations since natural gas is the major power source of this country. Unless other power source is developed, natural gas is our only hope. Almost all the existing processing plants are now operating beyond their capacities. Nonetheless there has been a dwindling situation in the gas production. Besides political indecision regarding new establishment of gas plant and other power source have made the situation nothing but complicated. In such a case an idea of optimization of the gas processing plant will surely pave a way to a sustainable solution. This project has the intention to carry out the simulation of the Bakhrabad gas processing plant (at Sylhet) using the Aspen-HYSYS process simulator. The steady state simulation of the gas processing plant shall be performed based on both the design and physical property data of the plant. DOI: http://dx.doi.org/10.3329/jce.v26i1.10186 JCE 2011; 26(1): 62-65